2017
DOI: 10.1111/ane.12832
|View full text |Cite
|
Sign up to set email alerts
|

Role of mHealth in overcoming the occurrence of post-stroke depression

Abstract: Depression associated with stroke affects roughly one-third of stroke survivors. Post-stroke depression (PSD) is thought to adversely influence functional outcome by limiting participation in rehabilitation, decreasing physical, social, and cognitive function, and affecting neuroplasticity thereby placing stroke survivors at high risk for future vascular events. PSD has also been associated with higher mortality rates after stroke. In Peru, a country where there is no national stroke program and mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…PSD occurs in one-third of stroke survivors [ 30 ] and has a negative effect on the restriction of participation in the rehabilitation process, decline in physical, cognitive, and social functions, and the biological process of neuroplasticity [ 31 ]. However, according to previous studies, many patients with PSD are not treated, and accordingly, innovative strategies to identify and treat PSD are needed [ 32 ]. One study in this review used TH-SM support as one of the approaches to PSD and demonstrated positive results [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSD occurs in one-third of stroke survivors [ 30 ] and has a negative effect on the restriction of participation in the rehabilitation process, decline in physical, cognitive, and social functions, and the biological process of neuroplasticity [ 31 ]. However, according to previous studies, many patients with PSD are not treated, and accordingly, innovative strategies to identify and treat PSD are needed [ 32 ]. One study in this review used TH-SM support as one of the approaches to PSD and demonstrated positive results [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, low levels of physical activity and motivation are known to hinder improvement in motor paralysis, sensory disturbance, higher brain dysfunction, and impairment in activities of daily living (ADL) (Kutlubaev and Hackett, 2014; Shimoda and Robinson, 2016). Mortality rates can be up to 10 times higher in patients with PSD than in those without (Miranda et al., 2018). According to a systematic review of previous studies, the reported prevalence of depression was 29%, with a cumulative incidence of 39–52% within 5 years of stroke (Ayerbe et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Post-stroke depression (PSD) is a severe and fearful complication that occurs in nearly one third of patients who suffer stroke and can even occur in patients who have suffered only a minor stroke or transient ischemic attack (TIA; Carnes-Vendrell et al, 2016 ). PSD can affect functional ability, rehabilitation outcome, and quality of life, and is related to a higher mortality rate of stroke patients (Miranda et al, 2018 ). Additionally, stroke severity is an important risk factor for PSD, as is the mental history of the patient.…”
Section: Introductionmentioning
confidence: 99%